RAGAM HIAS MOTIF BATIK MELALUI RELIEF FLORA CANDI BOROBUDUR PADA MAHASISWA PGSD FKIP UAD - Fery Setyaningrum; Heni Siswantari (Universitas Negeri Medan, 2021)
His study aims to describe the implementation of the decorative reliefs of the Borobudur temple flora on the batik motifs of PGSD FKIP UAD students. The research method that will be used is qualitative with a case study approach. Data collection techniques were carried out by interview, observation, and document review. Data analysis techniques that will be used in the form of data reduction, data presentation and drawing conclusions. The results of the study were the implementation of various relief batik motifs through the reliefs of the flora of the Borobudur temple on the work of PGSD UAD students. The motifs that appear in the decorative motifs made by students are geometric and non-gemetric batik motifs combined with flora reliefs in the form of frangipani trees, lotus trees, banana trees and lotus trees. Student works are in the form of 2-dimensional works with the identification of elements of straight, curved, zigzag and irregular lines, geometric expressions, organic expressions, multi-angled faces, and irregular shapes. and tertiary, playing dark and light, applying the principles of composition work.Keywords: Decorative Variety, Batik Motif, Relief